Molecular Mechanisms of Hawthorn Extracts in Multiple Organs Disorders in Underlying of Diabetes: A Review - Izadpanah Gheitasi; Feryal Savari; Ghaidafeh Akbari; Jamshid Mohammadi; Ali Reza Fallahzadeh; Hossein Sadeghi (International Journal of Endocrinology)
Diabetes mellitus (DM) is one of the most important metabolic disorders associated with chronic hyperglycemia and occurs when the body cannot manage insulin secretion, insulin action, or both. Autoimmune destruction of pancreatic beta cells and insulin resistance are the major pathophysiological factors of types 1 and 2 of DM, respectively. Prolonged hyperglycemia leads to multiple organs dysfunctions, including nephropathy, neuropathy, cardiomyopathy, gastropathy, and micro- and macrovascular disorders. The basis of the metabolic abnormalities in carbohydrate, fat, and protein in diabetes is insufficient action of insulin on various target tissues. Medicinal plants are rich sources of bioactive chemical compounds with therapeutic effects. The beneficial effects of leaves, fruits, and flowers extracts of Crataegus oxyacantha, commonly called hawthorn, belonging to the Rosaceae family, are widely used as hawthorn-derived medicines. Data in this review have been collected from the scientific articles published in databases such as Science Direct, Scopus, PubMed, Web of Science, and Scientific Information Database from 2000 to 2021. Based on this review, hawthorn extracts appear both therapeutic and protective effects against diabetic-related complications in various organs through molecular mechanisms, such as decreasing triglyceride, cholesterol, very low density lipoprotein and increasing the antioxidant activity of superoxide dismutase, catalase, glutathione peroxidase, total antioxidant capacity, decreasing malondialdehyde level, and attenuating tumor necrosis factor alpha, interleukin 6 and sirtuin 1/AMP-activated protein kinase (AMPK)/nuclear factor kappa B (NF-κB) pathway and increasing the phosphorylation of glucose transporter 4, insulin receptor substrate 1, AKT and phosphoinositide 3-kinases, and attenuating blood sugar and regulation of insulin secretion, insulin resistance, and improvement of histopathological changes in pancreatic beta cells. Collectively, hawthorn can be considered as one new target for the research and development of innovative drugs for the prevention or treatment of DM and related problems.